Wheat Response to Partially Acidified Phosphate Rock, Triple Super Phosphate and their Combinations in Vertisols in Sudan - EITilib, Abdelmoniem M.A.; A. Abdalla, Mubarak; E. Abdelhafeez, Mahgoub (Gezira Journal of Agricultural Science; Vol 1 No 1 (2003), 2021)
Conventional water soluble phosphorus fertilizers(PF) such as triple super phosphate (TSP) is expensive because it is an imported commodity. Therefore, it is wise to substitute it by a cheap local material where possible. Phosphate rock (PR) was found to be a suitable material as a source of phosphorus (P) for plants. To investigate this, a two year(Novermber1999 and 2000) field experiment with wheat ( Triticum aestivum L.), was carried out on a clay soil, in the Research Farm of the College of Agricultural Studies, University of Sudan. This was meant to test the agricultural value of using partially acidified phosphate rock (PAPR). Treatments consisted of two P sources (TSP and PAPR) applied at the rates of O, 43.0, 64.5 and 86.0 kg P 2 0 5 ha -1 Inoculation of wheat seeds with Vesicular arbuscular mychorrhiza   (VAM) was also tested to determine its effects on release of P from PAPR. Results showed that P APR, alone or in combination with TSP, significantly increased grain and straw yield over those of TSP alone by 31 to 41% and 9 to 18% in the two seasons, respectively. Phosphorus residual effect on yield of grain and straw of wheat was significantly higher in plots treated with PAPR compared to those treated with TSP. Inoculation of the seeds with VAM fungus did not show any significant effects on yield. It could be concluded that, mixing PAPR with TSP increased its effectiveness relative to PAPR alone, and therefore PAPR is proposed as a source of P for irrigated wheat in the Vertisols of the Sudan.